At the Origins of the Russophone Musical Folklore of Siberia (1920s–1940s) - Natalya A. Ursegova (Studia Litterarum)
The author examines the Soviet stage of the prehistory of Siberian musical folklore. The aim of the study is to reveal new musical collections that would be equivalent to their pre-revolutionary predecessors, analyze folklore sources, and evaluate their historical significance. Small number of records and publication of folk songs entailed a discussion of the problems of musical ethnography in the pages of the magazine Sibirskaya Zhivaya Starina in the mid-1920s. Unfortunately, in the period from 1926 to 1944, no valuable song collections (with the exception of the publication of prerevolutionary notes by N.P. Protasov) were added to the bibliography of Russian Siberian folklore music. Of special value is theoretical and practical (collecting) activity of G.S. Vinogradov. His works lay a theoretical foundation for the modern, the so-called “typological” trend in the study of Siberian folklore. The article accredits Vinogradov’s methodological approach to the collection of information about Siberian musicians and musical performance that engages ethnographers who do not have professional musical education.